Assets holding and financial performance of pension fund administrators in Nigeria (Journal of Economic Research & Business Administration, 2022)
Pension funds are founded to ensure contributors benefit from regular or lump sum income uponretirement. The financial performance of pension funds in Nigeria seems fraught with uncertainties, riskand delay in payment of benefits thus raising doubts whether they can be able to achieve their primaryobjective. This study was carried out to evaluate the relationship between assets holding and financialperformance of Pension Fund Administrators (PFAs) in Nigeria. 21 PFAs were examined under this studythrough judgmental sampling. The study sourced secondary data from PFAs. The data collected relates toinvestment in classes of asset and the investment reports on dividend income, interest income and rentalincome. The data was analyzed using correlational statistics to determine if there is a significant statisticaldifference in the asset classes and component of investment income. Assessments of association betweencomposition of the various pension fund portfolio and the amount of the various asset classes vis a vis theinvestment income earned were also made to find out if diversification of the portfolio affects the financialperformance of the pension funds. The research revealed that the collection of assets by the PFAs affectthe financial performance of the pension funds. From the analysis it is clear that assets holding is positivelyand statistically significant with the financial performance of PFAs. Therefore, it is very critical for PFAs toconsider the assets mix in the fund management without over-exposure to a particular asset.Key words: assets holding, financial performance, pension fund administrators.